Evidence for a ladder of investment in Central and Eastern European countries - Matt Hunt; Goran Serdarević; Tom Ovington; Clive Kenny (Charles University in Prague, Institute of Economic Studies (IES), 2014)
The model of liberalisation of European telecommunications markets had followed what has become known as the "ladder of investment" (LoI) hypothesis: under this hypothesis entrants are expected to make progressively greater investments in their own networks, whilst decreasing their dependence on the network of the incumbent fixed operator. The ultimate goal of the LoI approach is to achieve, where feasible, inter-platform competition. From a theoretical perspective, there are opposing forces at work: whilst offering retail services based on access to the incumbent's network at the 'first rung' of the ladder is less risky, access seekers may find that investing to step-up on the 'second and higher rungs' of the ladder too risky. It is therefore unclear from a theoretical perspective whether the LoI approach will lead to inter-platform competition. Whether and under what circumstances it would is thus an empirical question. Our paper focuses on the evidence for the LoI in Central and Eastern European (CEE) countries. Our analysis shows that the evidence available for CEE is consistent with entrants in CEE countries largely by-passing the LoI, by directly investing in their own networks. There are good reasons for this, as some of the assumptions underlying the LoI theory, such as good quality and universally available copper networks and relatively high cost and risk of investing in alternative infrastructure, do not necessarily hold in CEE countries. Our paper's results are broadly consistent with most of the existing literature and represents a valuable contribution by providing an insight into the applicability of the LoI to CEE countries.
Keywords: 330